Characteristics, prognostic factors, and chronological trends of out-of-hospital cardiac arrests with shockable rhythms in Taiwan – A 7-year observational study - Chi, Chien-Yu; Chen, Yen-Pin; Yang, Chih-Wei; Huang, Chien-Hua; Wang, Yao-Chang; Chong, Kah-Meng; Wang, Hui-Chih; Lien, Wan-Ching; Yang, Mei-Fen; Ma, Matthew Huei-Ming; Huang, Chien-Hua; Chen, Zheng-Cheng; et al. (Journal of the Formosan Medical Association, 2022)
The study aimed to explore the characteristics, predictors, and chronological trends of outcomes for adult out-of-hospital cardiac arrests (OHCAs) with shockable rhythms. A 7-year, community-wide observational study using an Utstein-style registry was conducted. Patients who were not transported, those who experienced trauma and those who lacked electronic electrocardiography data were excluded; those with initial shockable rhythms of ventricular fibrillation (VF) or pulseless ventricular tachycardia (pVT) were included. Outcomes were survival of discharge (SOD) and favorable neurological status (CPC 1–2). The outcome predictors, chronological trends, and their relationship with system interventions were analyzed. Of the 1544 shockable OHCAs (incidence 12.6%) included, 97.6% had VF and 2.4% had pVT. VF showed better outcomes than pVT. Predictors for both outcomes (SOD; CPC 1–2) were chronological change (adjusted odds ratio [aOR]: 1.133; 1.176), younger age (aOR: 0.973; 0.967), shorter response time (aOR: 0.998; 0.999), shorter scene time (aOR: 0.999; 0.999), witnessed collapse (aOR: 1.668; 1.670), and bystander cardiopulmonary resuscitation (BCPR) (aOR: 1.448; 1.576). Predictors for only SOD were public location (aOR: 1.450) and successful prehospital defibrillation (aOR: 3.374). The use of the supraglottic airway was associated with adverse outcomes. Chronologically with system interventions, BCPR rate, the proportion of shockable OHCA, and improved neurological outcomes increased over time. The incidence of shockable OHCA remained low in Asian community. VF showed better outcomes than pVT. Over time, the incidence of shockable rhythm, BCPR rate and patient outcomes did improve with health system interventions. The number of prehospital defibrillations did not predict outcomes.